Cerebral vasculitis due to Aspergillus spp. in immunocompromised patients: literature review - Elie Haddad; Arnaud Fekkar; Sophie Bonnin; Natalia Shor; Danielle Seilhean; Isabelle Plu; Valérie Touitou; Véronique Leblond; Nicolas Weiss; Sophie Demeret; Valérie Pourcher (International Journal of Infectious Diseases, 2022)
Objectives: Invasive aspergillosis is a threat for immunocompromised patients. We present a case series of aggressive cerebral vasculitis caused by Aspergillus spp. infection in immunocompromised patients. Methods: We present a retrospective case series of three autopsy-proven invasive cerebral aspergillosis with diffuse vasculitis affecting large caliber cerebral vessels. Results: Three patients were immunosuppressed: one on rituximab, one on corticosteroids, and one with a renal transplant. Two of these patients were diagnosed with cerebral aspergillosis on postmortem. Conclusion: Aspergillus cerebral vasculitis is a rare form of invasive aspergillosis that should be considered in an immunocompromised individual with suggestive lesions on imaging. It should be suspected as a possible cause of aseptic neutrophil meningitis.